SKAMs ’lige her’ og ’lige nu’ : Om SKAM og nærvær - Jerslev, Anne (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
The article discusses strategies for creating presence in space and time in SKAM, in particular the way the series unfolds as event and its extended use of close-ups. Moreover, the article discusses Bolter and Grusin’s understanding of immediacy and argues that the many mobile screens as well as the series’ cross-mediality, or hypermediacy, contribute to the creation of an impression of being close to the characters and their world, in time and space.